Improving Worker Health and Productivity: A Systematic Review of Participatory Ergonomics in Construction - Raharjo, Agung; Ariyanto, Januar; Jannah, Farahul (citeus, 2025)
The construction industry is recognized to be physically demanding and is characterized by a range of occupational safety and health issues, including musculoskeletal disorders (MSDs) arising from repetitive movements, prolonged static postures, and physically strenuous working conditions. Participatory ergonomic interventions in which workers are involved in the formulation of the problems have been recommended as effective interventions to increase productivity and health in industries. The objective of this literature review is to explore the effects of participatory ergonomics on health outcome and productivity measures in construction. The review followed the PRISMA 2020 guidelines and included nine studies which examined various ergonomic intervention approaches. Results indicated positive improvement in the reduction of MSDs and fatigue when there was high worker engagement. However, some studies reported limited effects on overall health or productivity. In conclusion, while participatory ergonomics shows potential, its long-term effectiveness depends on worker engagement, intervention design, and consistent implementation, indicating the necessity of a common language for outcome measure and long-term follow-up in future studies.